The Impact Of Bank Preferences On The Composition Of Loan Portfolios An Applied Study On A Sample Of Private Commercial Banks In Syria (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2020)
This study aims at demonstrating the effect of banks 'preferences on the formation of optimal loan portfolios for private Syrian commercial banks. The study was conducted for the period (2009 - 2018), where the researcher measured banks' preferences through (profitability preference, liquidity preference, safety preference) (as an independent variable), Return on loans and risk on loans (as dependent variables). The study used a deductive approach in the research as a whole, and then the survey design was used on a sample of private commercial banks in Syria, as for the method of data collection was used secondary data through reference to the annual reports and official statistics of commercial banks, and the statistical study of During the use of SPSS statistical software. The results of the study showed a variation in the effect of banks' preferences in the composition of the loan portfolios of Syrian private commercial banks (loan portfolio returns, loan portfolio risks), where there is a significant effect of the preference (liquidity) on the returns of the loan portfolios of Syrian private commercial banks under study. There is no significant effect on the liquidity and security preference on the risk of the loan portfolios of the banks under consideration, as well as there is no significant effect on the safety and profitability preference (rate of return on assets, rate of return on equity) on the returns of loan portfolios, while there is a significant effect to favor profitability (rate of return on Assets, rate of return on Equity) on the risk of loan portfolios for private Syrian commercial banks. هدفت الدراسة إلى بيان تأثير تفضيلات المصارف في تكوين محافظ القروض المثلى للمصارف التجارية السورية الخاصة، أجريت الدراسة للفترة (2009 –2018)، حيث قام الباحث بقياس تفضيلات المصارف من خلال ( تفضيل الربحية، تفضيل السيولة، تفضيل الأمان) (كمتغير مستقل)، العائد على القروض والمخاطر على القروض (كمتغيرات تابعة). اتبع الباحث المقاربة الاستنباطية في البحث ككل، ومن ثم تم استخدام تصميم البحث المسحي على عينة من المصارف التجارية الخاصة في سورية، أما بالنسبة لطريقة جمع البيانات تم استخدام طريقة البيانات الثانوية من خلال الرجوع إلى التقارير السنوية والإحصاءات الرسمية الخاصة بالمصارف التجارية، وتمت الدراسة الإحصائية من خلال استخدام البرنامج الإحصائي SPSS . اظهرت نتائج الدراسة وجود تباين في أثر تفضيلات المصارف في تكوين محافظ قروض المصارف التجارية السورية الخاصة (عوائد محافظ القروض، مخاطر محافظ القروض)، حيث يوجد أثر معنوي لتفضيل (السيولة) على عوائد محافظ قروض المصارف التجارية السورية الخاصة محل الدراسة، في حين أنه لا يوجد أثر معنوي لتفضيل السيولة والأمان على مخاطر محافظ قروض المصارف محل الدراسة، وكذلك لا يوجد أثر معنوي لتفضيل الأمان والربحية (معدل العائد على الأصول، معدل العائد على حقوق الملكية) على عوائد محافظ القروض، في حين يوجد أثر معنوي لتفضيل الربحية ( معدل العائد على الأصول، معدل العائد على حقوق الملكية) على مخاطر محافظ قروض للمصارف التجارية السورية الخاصة.